2019
DOI: 10.1111/obr.12904
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis estimating the population prevalence of comorbidities in children and adolescents aged 5 to 18 years

Abstract: SummaryEvidence for the health impact of obesity has largely focussed on adults. We estimated the population prevalence and prevalence ratio of obesity‐associated comorbidities in children and adolescents aged 5 to 18 years. Five databases were searched from inception to 14 January 2018. Population‐based observational studies reporting comorbidity prevalence by weight category (healthy weight/overweight/obese) in children and adolescents aged 5 to 18 years from any country were eligible. Comorbidity prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 56 publications
1
91
1
9
Order By: Relevance
“…2 Institute for Health and Sport, Victoria University, Melbourne, Australia. 3 Faculty of Science, Palacký University Olomouc, Olomouc, Czech Republic. 4 Alliance for Research in Exercise, Nutrition and Activity, School of Health Sciences, University of South Australia, Adelaide, Australia.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Institute for Health and Sport, Victoria University, Melbourne, Australia. 3 Faculty of Science, Palacký University Olomouc, Olomouc, Czech Republic. 4 Alliance for Research in Exercise, Nutrition and Activity, School of Health Sciences, University of South Australia, Adelaide, Australia.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…According to recent worldwide estimates, 6% of girls and 8% of boys are obese [1]. Obese children are at an increased risk of several physical and psychological comorbidities in their childhood and chronic illness and premature death later in life [2,3]. The origin of childhood obesity is complex, but the key contributing factor seems to be long-term dysregulation of energy balance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, if a healthy diet is promoted at a young age, this is more likely to track into adolescence and adulthood 32, 33 . The second reason is to prevent excessive weight gain, which could lead to overweight and obesity 34, 35 and increased risk of co‐morbidities 36 . A study by Syrad et al 13 found that in a UK twin birth cohort, a small (10 kcal) increase in meal size at 21 months was associated with a 4% faster growth rate above the average, demonstrating that increasing meal size was associated with more rapid weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Childhood obesity can have severe implications on a child's physical and mental health [3], which can continue into adulthood [1,4]. For example, prediabetes, high blood pressure [5], and depression [6]. Adopting healthy behaviours in the early years of a child's life ensures good development and growth [4].…”
Section: Introductionmentioning
confidence: 99%